Retraction Note: Laparoscopic repair of vesicovaginal fistulae with a transperitoneal approach at Universitas Gadjah Mada Urological Institute: a case report - Soeroharjo, Indrawarman (Springer Nature, 2022)
The Editor-in-Chief has retracted this case report because Figure 3a and Figure 3b are the same as Figure 2 and Figure 3 respectively in [1] which describes a different patient, and the text of the background and discussion sections shows overlap with [1,2,3,4]. Said Alfin Khalilullah and Prahara Yuri agree with this retraction. Indrawarman Soeroharjo and Raden Danarto have not responded to correspondence from the publisher about this retraction.